Learning Flash CS4 professional - Shupe, Rich (Sebastopol, Calif O'Reilly, 2009)
This book offers beginners and intermediate Flash developers a unique introduction to the latest version of Adobe's powerful multimedia application. This easy-to-read book is loaded with full-color examples and hands-on tasks to help you master Flash CS4's new motion editor, integrated 3D system, and character control with the new inverse kinematics animation system
"Getting up to speed with Flash."
Includes index
1
Keywords: Flash (Computer file); ActionScript (Computer program language); Computer graphics -- Computer programs; Digital video -- Editing -- Data processing; Web sites -- Design; Computer animation -- Computer programs